The Indian surrogate. - Muhammad Nurluqman Suratman. (2009)
An illustrated feature on the surrogacy industry of India. This report aims to explain the rationale for our final-year project (FYP) by framing the context of India's surrogacy industry. We intend to give readers a brief idea of the significant events that happened in the wombs-for-rent business hitherto and through our own interviews with industry experts we summarize the past and future of India's surrogate industry and its stakeholders. For the second part of this report, we also wish to discuss, in retrospect, the rationale behind our decisions, the objectives that we aim to achieve with our final year project, and the difficulties we encountered throughout the production of our book, The Indian Surrogate.